Naphthalonitriles featuring efficient emission in solution and in the solid state - Thulaseedharan Nair Sailaja, Sidharth; Maisuls, Iván; Kösters, Jutta; Hepp, Alexander; Faust, Andreas; Voskuhl, Jens; Strassert, Cristian A. (Beilstein Journal of Organic Chemistry, 2020)
In this work, a series of γ-substituted diphenylnaphthalonitriles were synthesized and characterized. They show efficient emission in solution and in the aggregated state and their environment responsiveness is based on having variable substituents at the para-position of the two phenyl moieties. The excited state properties were fully investigated in tetrahydrofuran (THF) solutions and in THF/H2O mixtures. The size of the aggregates in aqueous media were measured by dynamic light scattering (DLS). The steady-state and time-resolved photoluminescence spectroscopy studies revealed that all the molecules show intense fluorescence both in solution and in the aggregated state. In THF solutions, a blue emission was observed for the unsubstituted (H), methyl- (Me) and tert-butyl- (t-Bu) substituted γ-diphenylnaphthalonitriles, which can be attributed to a weak π-donor capability of these groups. On the other hand, the methoxy- (OMe), methylsulfanyl- (SMe) and dimethylamino- (NMe2) substituted compounds exhibit a progressive red-shift in emission compared to H, Me and t-Bu due to a growing π-electron donating capability. Interestingly, upon aggregation in water-containing media, H, Me and t-Bu show a slight red-shift of the emission and a blue-shift is observed for OMe, SMe and NMe2. The crystal structure of Me allowed a detailed discussion of the structure–property relationship. Clearly, N-containing substituents such as NMe2 possess more electron-donating ability than the S-based moieties such as SMe. Moreover, it was found that NMe2 showed higher luminescence quantum yields (ΦF) in comparison to SMe, indicating that N-substituted groups could enhance the fluorescence intensity. Therefore, the π-donor nature of the substituents on the phenyl ring constitutes the main parameter that influences the photophysical properties, such as excited state lifetimes and photoluminescence quantum yields. Hence, a series of highly luminescent materials from deep blue to red emission depending on substitution and environment is reported with potential applications in sensing, bioimaging and optoelectronics.
Keywords: aggregation caused quenching (ACQ); aggregation-induced emission enhancement (AIEE); naphthalonitriles (NCNs); solution and solid state emitters (SSSE); solvent quenching (SQ)